2009
DOI: 10.1016/j.molcel.2009.05.019
|View full text |Cite
|
Sign up to set email alerts
|

LysRS Serves as a Key Signaling Molecule in the Immune Response by Regulating Gene Expression

Abstract: Lysyl-tRNA synthetase (LysRS) was found to produce diadenosine tetraphosphate (Ap(4)A) in vitro more than two decades ago. Here, we used LysRS silencing in mast cells in combination with transfected normal and mutated LysRS to demonstrate in vivo the critical role played by LysRS in the production of Ap(4)A in response to immunological challenge. Upon such challenge, LysRS was phosphorylated on serine 207 in a MAPK-dependent manner, released from the multisynthetase complex, and translocated into the nucleus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
184
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(190 citation statements)
references
References 35 publications
6
184
0
Order By: Relevance
“…Collectively, these results suggested that regulation occurred due to negative feedback among TyrRS, PARP1, and SIRT1 under oxidative stress. In addition to their aminoacylation functions in protein synthesis, many aminoacyl-tRNA synthetases, including TyrRS, have been shown to take on multiple roles (41)(42)(43). Specifically, TyrRS was found to act as a sensor for oxidative stress after translocating to the nucleus, where it activates DNA damage repair genes that are downstream of E2F1 (7).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these results suggested that regulation occurred due to negative feedback among TyrRS, PARP1, and SIRT1 under oxidative stress. In addition to their aminoacylation functions in protein synthesis, many aminoacyl-tRNA synthetases, including TyrRS, have been shown to take on multiple roles (41)(42)(43). Specifically, TyrRS was found to act as a sensor for oxidative stress after translocating to the nucleus, where it activates DNA damage repair genes that are downstream of E2F1 (7).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has recently become clear that some human aaRSs also possess tissue-specific functions, distinct from their role in translation. Indeed, different aaRSs define pathways such as angiogenesis [TyrRS, TrpRS, and AIMP1 (44)(45)(46)], the immune response [LysRS (47)], inflammation [GluProRS (48)], apoptosis [GlnRS (49)], but also neural development [AIMP1, GlyRS, AIMP2 (50-52)], and tumorogenesis [LeuRS (53)]. The switch between the canonical aminoacylation function of an aaRS and other alternative functions might rely on a different process: (i) the oligomerization state, (ii) the subcellular localization, or (iii) the differential expression of the protein.…”
Section: A Previously Undescribed Model: Alternative Polyadenylation Ismentioning
confidence: 99%
“…We recently showed that LysRS, the main enzyme that produces Ap 4 A, translocates into the nucleus in activated mast cells (40). We hypothesized that Ap 4 A production occurs in the nuclei of activated mast cells, with concurrent Ap 4 A accumulation and LysRS nuclear localization.…”
Section: Ap 4 a Hydrolase Translocates Into The Nuclei Of Bmmcmentioning
confidence: 97%